Challenge-skills balance in international junior elite tennis players - Guinoubi, S.; Mouelhi-Guizani, S.; Chtara, M.; Crespo, M. (International Journal of Sports Science & Coaching, 2023)
This study uses self-determination and flow theories as a theoretical framework to investigate the role of need for competence satisfaction (NCS) and autonomous motivation (AM) in balance between challenge and skills (BCS) and dispositional flow (DF) in international junior elite tennis players. A sample of 114 (62 girls and 52 boys) junior elite players (15.62 ± 1.36 years) representing 24 countries competing in International Tennis Federation junior tournaments completed measures on the NCS using the Basic Needs Satisfaction in Sport Scale, AM with the Sport Motivation Scale and DF State scale to measure the BCS and their DF. Values of Cronbach a >.80 and the rhô Jöreskog coefficients were shown to be satisfactory and >0.89. The independent sample t-test analysis revealed no significant gender differences in any of them (p > .05). Simple regression analysis showed that there was a significant positive linear correlation between BCS and DF (r = .46; F = 29.31, p < .001). Multiple regression analysis indicated that AM and NCS explained 50.8% of the variance of BCS (F = 57.30, p < .001). Canonical correlation analysis indicated that a lack of NCS and AM was associated with a lack of DF and BCS. Wilks` lambda = .38, F = 34.11, p < .001, accounted for 99% (rc = .79) of the overlapping variance. It can be concluded that NCS and AM contribute effectively to the BCS and then to DF in the sample studied.